Gestión del conocimiento e innovación en las PYME exportadoras del sector industrial en Colombia (2017)
This article aims to analyze the relationship between knowledge management and identification of opportunities to innovate in industrial exporting SMEs in the Atlantic Department. It has a quantitative approach, descriptive scope, non-experimental cross-sectional design. We surveyed 39 managers selected with simple random sampling. It uses dispersion measures, location, and correlation coefficients. Evidence that the strategies of knowledge management are developed without theoretical foundations of organizational learning, TIC, and Intellectual Capital. It concludes that its articulation, supports innovation